Engineering Properties Of Lightweight Foamed Concrete With 25 % And 50 % Ceramic Tile Wastes As Partial Cement Replacement Materials - Ng, Wen Wei (2020)
Production of concrete emits greenhouse gases which aggravate global warming. In the meanwhile, ceramic tile wastes generated from manufacture factory, construction site and building demolition project dispose of by landfill create land and water pollution. In this study, the suitability of ceramic tile wastes to partially replace cement in the lightweight foamed concrete is investigated with the aim to discover a greener construction material. Three types of lightweight foamed concrete with 0 %, 25 % and 50 % ceramic tile wastes as partial cement replacement materials were prepared with a target density of 1200 kg/m3 , namely LFC-CTW0, LFC-CTW25 and LFC-CTW50. The effects of ceramic tile wastes on the engineering properties of lightweight foamed concrete were investigated by the conduction of fresh density determination, flow table test, inverted slump test, compressive strength test, splitting tensile strength test, flexural strength test, modulus of elasticity and Poisson’s ratio test, as well as compressive toughness test. The mechanical properties of concrete specimens were water cured and tested at the concrete ages of 7, 28 and 56 days. Results from the lab experiments showed that the incorporation of 25 % ceramic tile wastes into lightweight foamed concrete was comparably feasible than 50 %. LFC-CTW25 performed better than LFC-CTW0 for flexural strength test and splitting tensile strength test at Day-56. Compressive strength, elasticity modulus and compressive toughness reduced while Poisson’s ratio increased for foamed concrete incorporated with ceramic tile wastes. LFC-CTW25 is predicted to achieve better than control mix with curing period greater than 56 days.